Effect of Different Dielectric Fluids on Micro EDM of Low Conductivity Ceramic Material RB-SiC - Liew, Pay Jun; Yan , Jiwang; Masaki, Takeshi; Kuriyagawa, Tsunemoto (Trans Tech Publications, 2012)
The machining characteristics of reaction bonded silicon carbide (RB-SiC) in micro electrical discharge machining process were studied by using EDM oil, deionized water, and graphite fiber mixed EDM oil as the dielectric fluids. The process performances were measured in terms of material removal rate, surface roughness and surface topography. The effect of deionized water on SUS 304 also was tried and compared with that on RB-SiC. It was found that when graphite fiber mixed EDM oil was used, higher material removal rate, better surface finish and smoother surface topography were obtained compared to that pure EDM oil and deionized water on RB-SiC. Deionized water could produce better form accuracy, however, electrolytic corrosion occurred and small pits were formed around the machining area of RB-SiC. In contrast, electrolytic corrosion was insignificant for SUS 304.